Reliability of ultrasound in the assessment of muscle thickness in critically ill children - Jéssica Knisspell de Oliveira; Camila Wohlgemuth Schaan; Cristiano Kohler Silva; Taila Cristina Piva; Ian Teixeira e Sousa; Francisco Bruno; Janice Luisa Lukrafka (Elsevier, 2023)
Introduction: Ultrasound has been used to quantify and qualify muscle morphology in critically ill children and can detect changes in muscle thickness. The aim of this study was to assess the reliability of ultrasound measurement of muscle thickness in critically ill children and to compare the assessments made by an expert with those made by inexperienced sonographers. Material and methods: Cross-sectional observational study conducted in the paediatric intensive care unit of a tertiary care university hospital in Brazil. The sample included patients aged 1 month to 12 years who received invasive mechanical ventilation for at least 24 h. Ultrasound images of the biceps brachii/brachialis and quadriceps femoris were obtained by one experienced sonographer and several inexperienced sonographers. We assessed intrarater and inter-rater reliability by means of the intraclass correlation coefficient (ICC) and Bland-Altman plot analysis. Results: Muscle thickness was measured in 10 children with a mean age of 15.5 months. The mean thickness of the assessed muscles as 1.14 cm for the biceps brachii/brachialis (standard deviation [SD], 0.27) and 1.85 cm for the quadriceps femoris (SD, 0.61). The intrarater and inter-rater reliability were good for all sonographers (ICC > 0.81). The differences were small, there was no significant bias in the Bland-Altman plots and all measurements were within the limits of agreement, except for 1 measurement of biceps and quadriceps. Conclusion: Sonography can be used in critically ill children to accurately assess changes in muscle thickness, even by different evaluators. More studies are needed to establish a standardised approach to the use of ultrasound for monitoring muscle loss in order to incorporate it in clinical practice. Resumen: Introducción: La ecografía se ha utilizado para cuantificar y calificar la morfología muscular de niños críticamente enfermos, detectando posibles cambios en el grosor muscular. El objetivo del estudio fue evaluar la fiabilidad de la medición por ecografía del grosor muscular en niños críticamente enfermos y comparar la evaluación de un examinador experto con la de examinadores con poca experiencia. Material y métodos: Estudio observacional transversal en la unidad de cuidados intensivos pediátricos de un hospital universitario de tercer nivel en Brasil. Se incluyeron pacientes entre 1 mes y 12 años que recibieron ventilación mecánica invasiva durante un mínimo de 24 horas. Se obtuvieron imágenes ecográficas del bíceps braquial/braquial y cuádriceps femoral en evaluaciones realizadas por un ecografista experimentado y ecografistas inexpertos. La concordancia intra- e interevaluador se estableció mediante el coeficiente de correlación intraclase (CCI) y el análisis gráfico de Bland-Altman. Resultados: Se midió el grosor muscular en 10 niños con una edad media de 15,5 meses. El grosor medio de los músculos evaluados fue de 1,14 cm ± 0,27 para el bíceps braquial/braquial y de 1,85 cm ± 0,61 para el cuádriceps femoral. La fiabilidad intraevaluador e interevaluador fue muy buena (CCI > 0,81) para todos los ecografistas. Las diferencias fueron pequeñas, sin detectarse en el análisis de los gráficos de Bland-Altman, y todas las mediciones estuvieron dentro de los límites de concordancia, excepto una medición de bíceps y cuádriceps. Conclusión: La ecografía se puede utilizar en niños en estado crítico para evaluar con precisión los cambios en el grosor muscular, incluso por diferentes evaluadores. Se necesitan más estudios para establecer un enfoque estandarizado en el uso de esta herramienta para la monitorización de la pérdida muscular con el fin de incorporar su uso en la práctica clínica.